An evaluation of compliance of Mass Drug Administration (MDA) against Lymphatic Filariasis of Satna district of Madhya Pradesh, India - Rohit, Trivedi; Sandeep, Singh; Paharam, Adhikari; Sukhendra, Pratap Singh; Manoj, Saxena (Universiti Kebangsaan Malaysia, 2015)
Introduction: Mass drug administration (MDA) means once-in-a-year administration of Diethyl Carbamazine (DEC) tablet to all people (excluding children under 2 years, pregnant women and severely ill persons) in identified endemic areas. It aims at cessation of transmission of Lymphatic Filariasis. To study the coverage and compliance of MDA in Satna district during the campaign in June 2013. Methods: Cross-sectional observational study. Setting: Urban And Rural Areas In Satna District Identified As Endemic For Filariasis Where MDA 2013 Was Undertaken. Study Variables: Exploratory - Rural and urban clusters of Satna district; Outcome - coverage, compliance, actual coverage, side effects. Results: Four clusters, each comprising 30 households from the Satna endemic district, yielded an eligible population of 650 (95.87%) of total 678. The coverage was 586 (90.15% out of eligible population) with variation across different areas. The compliance with drug ingestion was 88.05% with a gap of 11.95% to be targeted by intensive IEC. The effective coverage (79.38%) was below the target (85%). Side effects of DEC were minimum, transient and drug-specific. Conclusions: Overall coverage was marginally better in rural areas. The causes of poor coverage and compliance have been discussed and relevant suggestions have been made.